Contamination of tap water sources to Acanthamoeba spp. in selected cities of Hormozgan province, Iran - Niyyati, Maryam; Jonaydi, Zaynab; Behniafar, Hamed; Valai, Naser (Researcher Bulletin of Medical Sciences, 2018)
Background Free-living amoeba (FLA) such as Acanthamoeba are ubiquitous and amphizoic protozoan parasites. These parasites can cause severe human infections. Water resources are one of the important habitats for FLAs. Waters in tanks and wells can be a habitat for Acanthamoeba species, particularly in warm climates. The present study was conducted to evaluate the presence of Acanthamoeba species in tap water resources of selected cities of Hormozgan Province, Southern Iran. Material and methods In this cross sectional study, 50 water samples (approximately 500 mL) were collected from tap water resources (25 samples from tanks and 25 samples from wells) of Hormozgan province. The samples were filtered, cultured on 1.5% non-nutrient agar medium. After incubation at room temperature, cloning was performed. Investigation of Acanthamoeba species was performed using the microscopic method and page key. Results Out of 50 samples, 14 samples (28%) were found positive. Out of 25 examined well samples 9 samples (36%) were found contaminated with Acanthamoeba spp., while only 5 (20%) of 25 tank samples were found positive. All samples were cloned successfully. Conclusion The high occurrence of Acanthamoeba spp. in water resources of Hormozgan province could be as a hazard for public health of the region, and using effective disinfectants and accurate monitoring may be a good suggestion.